COMPARISON OF LOW OSMOLAR ORAL REHYDRATION SOLUTION VERSUS STANDARD ORAL REHYDRATION SOLUTION IN CHILDREN WITH ACUTE DIARRHOEA IN RELATION TO UNSCHEDULED INTRAVENOUS FLUID REQUIREMENT - Tahir, Sidra; Iqbal, Rabia; Najam, Rabia; Kamran, Muneeba; Anwar, Najwa (Pakistan Armed Forces Medical Journal, 2021)
Objective: To determine requirement of unscheduled I/V fluid in children treated with low osmolar oral rehydration solution as compare to standard oral rehydration solution. Study Design: Case control study. Place and Duration of Study: Department of Paediatrics, Lahore General Hospital, Lahore, from Sep 2018 to Feb 2019. Methodology: Sample size of 400 patients was calculated using WHO calculator. Patients were recruited through non probability consecutive sampling. Patients were randomly divided into two groups. For each patient detailed history was taken including demographic information. Group A patients (controls) receive standard oral rehydration solution and Group B patients will receive low osmolar oral rehydration solution (Cases). Each group was followed for 6 hours after the treatment. Data analysis was done using SPSS version 24. Chi-square test applied and p-value ≤0.05 found significant. Results: A total of 400 cases were enrolled in the study. There were 220 (55%) male and 180 (45%) female in our study. Mean weight of patients was 9.46 Kg ± 5.9 SD. In group A, 8 patients showed unscheduled fluid requirement while 192 did not showed unscheduled fluid requirement. In group B, 32 patients showed unscheduled fluid requirement while 168 did not showed unscheduled fluid requirement (p=0.000). Conclusions: Incidence of or need of, unscheduled I/V fluid in children treated with low osmolar oral rehydration solution is less as compare to standard oral rehydration solution for management of acute diarrhea with some dehydration. And hence low osmolar oral rehydration solution shows better acceptance in management of acute diarrhea.